Appendiceal lesions in serrated polyposis patients are easily overlooked but only seldomly lead to colorectal cancer - van Toledo, David E. F. W. M.; IJspeert, Joep E. G.; Bleijenberg, Arne G. C.; Bastiaansen, Barbara A. J.; van Noesel, Carel J. M.; Dekker, Evelien (Endoscopy, 2023)
Background Serrated polyposis syndrome (SPS) is the most prevalent colonic polyposis syndrome and is associated with an increased colorectal cancer risk. A recent study in resected appendices of SPS patients reported that 6/23 (26.1 %) of identified serrated polyps had histological dysplasia. We evaluated the prevalence and clinical relevance of appendiceal lesions in a large SPS cohort.Methods Prospective data from 2007 to 2020 for a cohort of 199 SPS patients were analyzed. Data were retrieved from endoscopy and pathology reports. Patients who underwent (pre)clearance colonoscopies, surveillance colonoscopies, or colorectal surgery including the appendix were separately evaluated for the presence of appendiceal lesions. The primary outcome was the prevalence of adenocarcinomas and serrated polyps/adenomas with advanced histology in the surgery group.Results 171 patients were included, of whom 110 received endoscopic surveillance and 34 underwent surgery. Appendiceal lesion prevalence in the surgery group was 14 /34 (41.2 %, 95 %CI 24.7 %–59.3 %); none were advanced on histology. Detection rates in the (pre)clearance group were 1 /171 (0.6 %, 95 %CI 0.01 %–3.2 %) for advanced and 3 /171 (1.8 %, 95 %CI 0.04 %–5.0 %) for nonadvanced appendiceal lesions, all of which were sessile serrated lesions. During 522 patient-years of surveillance, no advanced appendiceal lesions were detected at endoscopy, and in 1 /110 patients (0.9 %, 95 %CI 0.02 %–5.0 %) was a nonadvanced lesion detected.Conclusion Appendiceal lesions are common in SPS patients. The discrepancy between the endoscopic detection rate of appendiceal lesions and the reported prevalence in surgically resected appendices suggests a substantial miss-rate of appendiceal lesions during colonoscopy. Advanced appendiceal lesions are however rare and no appendiceal adenocarcinomas occurred, implying limited clinical relevance of these lesions.